(untitled) (Development Service Industry Management, 2024)
Diversification covers a wide range of aspects, from the characteristics of production diversification to the assessment of factors that influence the decision to implement it. This concept is an integral part of the organizational and economic mechanism of the functioning of business structures and includes the classification of diversification types and the analysis of their financing sources. The article considers the stages of diversification, the main directions of diversification in modern conditions and characterizes diversification methodsBusiness diversification means the strategic expansion of a company into new products, services or markets in order to reduce risk, take advantage of new opportunities and increase the overall sustainability of the business. The purpose of diversification is often to reduce the overall risk of business and create new sources of income, which became the basis for the study of the theoretical foundations of the implementation of the strategy of diversification of business structures in the modern conditions of a changing, uncertain environment. A deep understanding of diversification processes allows enterprises to develop effective development strategies that take into account both the company’s internal resources and external factors. Through research, businesses can identify new opportunities for growth, innovate and meet customer needs.Diversification is a powerful tool for ensuring the sustainable development of enterprises in conditions of high competition and a changing external environment. It allows you to reduce risks, increase competitiveness, adapt to changes and ensure stable growth. However, diversification requires careful planning and analysis, as rash decisions can lead to negative consequences. Therefore, it is necessary to carefully choose diversification strategies for the effective functioning of companies.